A super absorbent polymer containing copper to control Plenodomus tracheiphilus the causative agent of mal secco disease of lemon - El boumlasy, Soumia; La Spada, Federico; Pane, Antonella; Licciardello, Antonino; Debdoubi, Abderrahmane; Tuccitto, Nunzio; Cacciola, Santa Olga (Frontiers in Microbiology, 2022)
The aim of this study was to determine the effectiveness of a Super absorbent polymer (SAP) containing copper (SAP-Cu) in controlling mal secco disease of lemon caused by the fungus Plenodomus tracheiphilus. SAP-Cu was characterized by atomic absorption spectrometry (AAS) and UV-VIS spectroscopy. In vitro tests were performed to determine the inhibitory effects of SAP-Cu against the pathogen on both potato-dextrose-agar medium and naturally infected lemon cuttings. SAP was able to absorb up to about 200 and 30 times its weight of ionized water and copper (II) sulfate solution (Cu2+ ions at the concentration 236 mM), respectively. The distribution of copper released on twigs after 24 hours of contact with SAP-Cu was determined by secondary ion mass spectrometry with time-of-flight analyzer (ToF-SIMS). SAP-Cu significantly inhibited the viability of P. tracheiphilus in lemon twigs. Overall, the results of this study showed that the SAP could be a suitable carrier of antifungal compounds.